A "Solid Dual‐Ions‐Transformation" Route to S, N Co‐Doped Carbon Nanotubes as Highly Efficient "Metal‐Free" Catalysts for Organic Reactions. Issue 48 (17th October 2016) - Wang, Fan; Song, Shuyan; Li, Kai; Li, Junqi; Pan, Jing; Yao, Shuang; Ge, Xin; Feng, Jing; Wang, Xiao; Zhang, Hongjie
Abstract : A green and cost‐effective method, named the "solid dual‐ions‐transformation reaction", is reported to achieve the goal of successfully doping S and N into hollow carbon nanotubes. No harmful raw material is needed during the whole synthesis. Importantly, in the catalytic test of chemical reduction of p ‐nitrophenol by NaBH4, the as‐obtained S, N co‐doped hollow carbon nanotubes exhibit ultrahigh catalytic performances.